PROSES BERPIKIR DUA SISWA SMP DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI DOMINASI OTAK KIRI DAN OTAK KANAN - Santoso Yohanes, Rudi (Widya Warta, 2013)
This research aims to determine the thinking process of the junior high school students to solve mathematic problems in terms of the dominance of the left hemisphere and the right hemisphere.The subject of this study is a student whose left brain is dominant and a student whose right brain is dominant. The two students were selected from 10 junior high school students who took mathematic olympiad training fostered by the researcher.To determine the student whose left brain is dominant and the one whose right brain is dominant, Hemispheric Dominance Inventory Test was applied. While, to describe the thinking process of students in solving mathematic problems, the researcher analyzed and interpreted the steps used by students with Thinking Aloud method.The result of this research indicated that the student whose left brain is dominant tended to make use of analytic, deductive, linear and systematic approaches. Meanwhile, the student whose right brain is dominant tended to make use of visual, inductive, randomized, and divergent approaches.